2015
DOI: 10.1021/acsami.5b09231
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Postdeposition Treatment-Induced Band Gap Widening at Cu(In,Ga)Se2 Surfaces – Reason for Performance Leap?

Abstract: Direct and inverse photoemission were used to study the impact of alkali fluoride postdeposition treatments on the chemical and electronic surface structure of Cu(In,Ga)Se2 (CIGSe) thin films used for high-efficiency flexible solar cells. We find a large surface band gap (E(g)(Surf), up to 2.52 eV) for a NaF/KF-postdeposition treated (PDT) absorber significantly increases compared to the CIGSe bulk band gap and to the Eg(Surf) of 1.61 eV found for an absorber treated with NaF only. Both the valence band maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
205
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 155 publications
(232 citation statements)
references
References 31 publications
23
205
4
Order By: Relevance
“…[25] It was found that similar to a KF PDT, a surface layer forms. [5][6][7][8][9]26,30] Additionally, as presented here for a RbF PDT, with the introduction of a KF PDT, a blocking of the diode current was observed. [15] Recently, Malitckaya et al calculated the bandgap energies of AlkInSe 2 (Alk = Li, Na, K, Rb, Cs) secondary phases, which are expected to segregate on the surface of the CIGS absorber for K, Rb, and Cs.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…[25] It was found that similar to a KF PDT, a surface layer forms. [5][6][7][8][9]26,30] Additionally, as presented here for a RbF PDT, with the introduction of a KF PDT, a blocking of the diode current was observed. [15] Recently, Malitckaya et al calculated the bandgap energies of AlkInSe 2 (Alk = Li, Na, K, Rb, Cs) secondary phases, which are expected to segregate on the surface of the CIGS absorber for K, Rb, and Cs.…”
Section: Discussionsupporting
confidence: 67%
“…A surface bandgap widening was observed after a KF PDT also experimentally. [8,9] These results hint to the fact that similar to a KF PDT, a RbF PDT introduces a surface layer, which might be responsible for the blocking of the diode current. That Rb-containing surface layer is subsequently called RIS layer.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[7], [10], [11] Furthermore, it was shown that this treatment has a distinct effect on the electronic surface structure of CIGSe absorbers. [8], [10] We have previously found a pronounced surface band gap (Eg surf ) wideningexplained by the formation of the Cu-and Ga-depleted surface and a K-In-Se type surface species -resulting in Eg surf =(2.52[+0.14/-0.51] eV).…”
Section: Introductionmentioning
confidence: 99%
“…The Cu-depleted layer was found to have a wider surface band gap than untreated absorbers [16,19] [24e26]). Whether the ion exchange reaction is limited to the grain boundaries or appears also in the bulk is not known currently.…”
Section: Alkali Treatmentmentioning
confidence: 99%